End to End IP QoS Assurance Using Policy Based Multi-Agents SLA Management Systems 10.14209/jcis.2003.3 - Fonseca, Mauro; Agoulmine, Nazim (Journal of Communication and Information Systems, 2015)
The development of Internet as well as overall communication technologies has created a very competitive communication market. In fact, there is no doubt that in the near future, every company and perhaps every person in the world will have an physical or wireless Internet access via an ISP (Internet Service Provider). Thus, the Internet became a very complex global network which represents an opportunity to provide worldwide value-added services requiring a certain level of quality of service (QoS) such as QoS-VPN (Virtual Private Network), VoD (Video On Demand). telelearning, e-Cornmerce, etc. Thus, we propose in this work to extend this approach in order to integrate new mechanisms that will allow customers to request end-to-end services. This assurance covers the QoS as well as associated parameters such as cost. The proposed solution introduces interoperability mechanisms between ISP policy based management systems and uses mobile agents to facilitate the negotiation between domains. The agent negotiation process is constrained by a set of predefined policies in order to limit the boundaries of the SLA parameters such as the cost. QoS, etc.